The Transition to a Market Economy: Financial Options - Hyman P. Minsky (Levy Economics Institute of Bard College, 1991)
The social transformation of Eastern Europe has proceeded much faster, and the destruction of communism's legitimacy and efficacy has been more complete, than was deemed possible even a few years ago. A common tenet among the economies now emerging from communism is the lack of significant private wealth, even though there are capital assets that are used in production and have the potential to generate profits. However, since there is no relevant history of profits in the emerging economies, there is no way to meaningfully assess values of capital assets. The financial system provides for linkages through time: Exchanges of money for well-defined claims to future-money flow are made daily. Thus, the financial structure and the physical capital assets of a capitalist economy link the present and the past to the future. The options available to the emerging economies with respect to their financial structure are limited-the lack of significant private wealth leads to weak market for financial instruments and poor prospects for market-based financing. The initial choice of a financial structure is constrained to universal banks or public holding companies. Special venture capital holding companies and local independent banks should be integrated into the financial structure to facilitate entrepreneurial spirit. The public holding company is favored as a transitional instrument to foster the development of information and private wealth, and should be modeled after the Reconstruction Finance Corporation of the New Deal era.
Keywords: 330